Determinant of Intellectual Capital Disclosure in Indonesian Listed Companies - Meiriza, Nahda; Lukviarman, Niki; Setiany, Erna (Jurnal Akuntansi dan Bisnis, 2022)
This study aims to evaluate and analyze the factors (firm size, profitability, leverage, audit firm type, and industry type) of intellectual capital disclosure (ICD) in the annual reports of Indonesian listed businesses. The information was extracted from the 2020 annual reports of 71 selected publicly traded corporations. The sample technique incorporated stratified sampling. In this study, multiple linear regression analysis models are used for model analysis. The conclusions that can be derived from this study based on the data analysis findings and the prior discussion are that firm size and industry type were proven to be determinants of ICD in the annual reports of Indonesian listed companies, implying that they have some influence on the ICD. Conversely, the findings of this study's variables for profitability, leverage, and audit firm type indicate that these factors have no significant impact on the extent of ICD. Penelitian ini bertujuan untuk mengevaluasi dan menganalisis faktor-faktor (ukuran perusahaan, profitabilitas, leverage, jenis perusahaan audit, dan jenis industri) dari pengungkapan modal intelektual (ICD) dalam laporan tahunan perusahaan terdaftar di Indonesia. Informasi tersebut diambil dari laporan tahunan tahun 2020 dari 71 perusahaan publik terpilih. Teknik pengambilan sampel yang digunakan adalah stratified sampling. Dalam penelitian ini, model analisis regresi linier berganda digunakan untuk analisis model. Kesimpulan yang dapat diambil dari penelitian ini adalah bahwa ukuran perusahaan dan jenis industri terbukti menjadi penentu ICD dalam laporan tahunan perusahaan yang terdaftar di Bursa Efek Indonesia, yang menyiratkan bahwa mereka memiliki pengaruh terhadap ICD. Sebaliknya, temuan variabel penelitian ini untuk profitabilitas, leverage, dan jenis perusahaan audit menunjukkan bahwa faktor-faktor ini tidak berpengaruh signifikan terhadap tingkat ICD.